How Good Is Online Information for Patients on the Treatment for Luminal Gastrointestinal Cancers? A Comprehensive Evaluation in English and Spanish - Beas, Renato (2023)
The internet has become a necessary communication platform for health information. The quality of online material for patients varies significantly, and this is not different for material on gastrointestinal cancers. We aimed to assess English and Spanish online patient information addressing esophageal, gastric, and colorectal cancer treatment. Six independent Google searches were conducted using the terms: esophageal cancer treatment, gastric cancer treatment, colorectal cancer treatment, and their translations in Spanish. Websites were included in the top 50 results for each search. Readability was assessed using two validated tests for each language. Understandability/actionability, quality, and cultural sensitivity were assessed using Patient Education Materials Assessment Tool (PEMAT), DISCERN, and Cultural Sensitivity Assessment Tool (CSAT), respectively. Pearson’s chi-squared was used for categorical variables and Wilcoxon rank-sum (2 groups) or Kruskal–Wallis (> 2 groups) for continuous. One hundred twelve websites were analyzed. Readability levels were high in both languages (between 11th grade and university level) and significantly higher in English. Mean quality scores for English and Spanish were consistent with good quality. CSAT scores met the cultural acceptability with lower CSAT scores for gastric cancer treatment in English. Higher actionability scores were found in English for colorectal cancer. Also, there was a clear trend for higher cultural sensitivity and quality of Spanish material for gastric cancer treatment. Online patient information on esophageal, gastric, and colorectal cancer treatment, in English and Spanish, were at a readability level above the average literacy level and even significantly higher in English. Initiatives to improve online information on gastrointestinal cancer treatments are warranted.